(3bUjOI aj gLGA CMeO Hf YdjhI GdeSJZGfejs - (3eMeO Hf bGSe GdHGQSjGdCfOdSj GdCfUGQj GdYHGSjs
(3ChdgG (B:s
(3HYV eG bdJg ef HMQ GdWhjd(B: (3ef Pdc bUjOI ai gLh HYV GdeqOYjf HeSJZGfe CYGOgG Gddg OGQ GdSdGe s
(3BNQgG (B:s
(3hef MGO YfgeG adG Tc Cfg jejd Edi GYJbGO Cgd GdWHjYI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B154 - (3U(B156s
(3GdeNWhWI HgG VHWs
(3HgG fXGe GdJYbjHIs
(3hJdGgG QSGFd djSJ aj GdCOHs
(3Ydi ZdGa GdeNWhWI Cfg cfGT GTJed Ydi HYV GdbUGFO dcGJHg eMeO Hf bGSe heG CKHJfGg gh GdUMjM s
(3cGf GdeDda MjkG SfI (B1329(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs